Digital Transformation in the Age of Industry 4.0: Acceleration of Transformational Performance through Business Model Innovation and Co-Creation Strategy in Indonesia ICT Firm - W Wasono M, Leonardus; ., Elidjen; ., Firdaus; ., Alamsjah; ., Sasmoko (International Journal of Engineering and Technology, 2019)
Industry 4.0 has significant impact in accelerating the firm performance across industries. This paper aims to discuss how the ICT firm could manage the transformational performance by integrating the business model innovation and co-creation strategy. The construction model of Transformational Performance and Co-creation strategy is expected to contribute to theory of performance and co-creation. Both of literature based on Indonesia ICT phenomenon. Indonesia ICT Industry has gained attention to be studied since it is one of the emerging markets that has the unique market characteristics. It has numerous opportunities but lack with the digital infrastructure. The digital transformation is required to assure the firm could sustain their business. Measurement of the succeed in implementing transformation is one of key success factor. The construction of transformational performance variable is driven from theory of quality management, balance score card and digital maturity. This construct could contribute as a reference model for tracking transformational firm performance. In digital transformation and disruptive era, business model and co-creation are key factors to drive performance. Business model innovation through collaboration and partnership, called as co-creation is the integrated strategy to perform in the market. In order to elaborate model, we develop prototype using 35 samples of Indonesia ICT Firm senior leader. The statistical used to analyze through Partial Least Square (PLS). The finding shows that firms transformational performance is significantly influenced by business model innovation and co-creation strategy. Further finding shows that in digital transformation, the all core capability could not be fulfilled by firm, it requires the collaboration and it could be created crowd-sourced. Our selected examples are only prototypical of research model and our implications are limited to their particular context. Ultimately, our research model requires further research and validation. However, our work allows us to develop further research and testing.Â Â